Concealed and Unconcealed Motives for Joining the Parent-Teacher Association: Mapping Sentence and Smallest Space Analysis - Fisher, Yael (Frontiers in Psychology, 2018)
Background & Subject: A Parent-Teacher Association (PTA) is an organization that enables parents to be involved in their children’s schools. Participation in the PTA is one of many steps parents can take to ensure their involvement. Few if any studies have examined parents' concealed and unconcealed motives for joining the PTA. Purpose / Hypotheses: The main purpose was to identify the structure of the concept Motives for Joining the PTA, so as to enhance our understanding of what motivates Israeli parents to join the PTA. The second purpose was to differentiate between parents' concealed and unconcealed motives. Method / procedure: A self-report anonymous questionnaire, containing 37 items, was administrated. Data were collected from a sample of 155 Israeli parents. The initial data processing stage involved EFA (Exploratory factor analysis) using SPSS software. Stage two was a Smallest Space Analysis (SSA), conducted using the Hebrew University Data Analysis Program (HUDAP). Results: EFA indicated three main factors. The internal consistency of the scores in the entire scale, measured using Cronbach's alpha coefficient, was 0.89. Data deployment on the SSA map exhibited both a polarized form (an angular form) and a radial form in a Radex configuration. The first layer (the polarized facet) was composed of three major motives related to self-serving altruistic ideological motives/ (SSAIM), self-serving altruistic pedagogical motives (SSAPM), and egoistic motives (EM). The second layer (the radial form) was composed of concealed motives, unconcealed motives, and politically-correct-driven motives.